CDR clipping-induced heterodimerization: identification of a novel dimerization mechanism in a co-formulated antibody cocktail via a multifaceted mass spectrometry approach - Andrew J Heindel; Yang Shen; Timothy N Tiambeng; Yuetian Yan; Shunhai Wang; Ning Li (mAbs)
Co-formulated antibody cocktails are becoming an increasingly popular therapeutic class; however, they present analytical challenges over traditional single monoclonal antibody (mAb) formulations. One paramount concern is the formation of heteromeric species that have unknown impacts on safety and efficacy. Consequently, effective approaches for identifying and characterizing high-molecular weight (HMW) impurities are critical to the successful development of this therapeutic class. In this study, we used a multifaceted mass spectrometry approach to characterize a unique dimer species formed between two co-formulated mAbs under thermal stress, revealing an intriguing dimerization mechanism that is driven by complementarity-determining region clipping-induced domain swap. Size exclusion chromatography-mass spectrometry, complemented by post-column denaturation, was utilized at both intact and subunit levels to pinpoint the dimerization interface. Additionally, by probing the disulfide bond susceptibility changes via limited reduction and middle-down analysis, the structural changes of the involved domains were studied. These results highlight the critical role of sophisticated analytical methods in comprehending and addressing the complexities linked to co-formulated mAb cocktails.